Detection of interaction between biomineralising proteins and calcium carbonate microcrystals - Rademaker, Hanna; Launspach, Malte (Beilstein Journal of Nanotechnology, 2011)
The natural composite nacre is characterised by astonishing mechanical properties, although the main constituent is a brittle mineral shaped as tablets interdispersed by organic layers. To mimic the natural formation process which takes place at ambient conditions an understanding of the mechanism responsible for a defined microstructure of nacre is necessary. Since proteins are assumed to be involved in this mechanism, it is advantageous to identify distinct proteins interacting with minerals from the totality of proteins contained in nacre. Here, we adopted and modified a recently published approach given by Suzuki et al. that gives a hint of specific protein–mineral interactions. Synthesised aragonite or calcite microcrystals were incubated with a protein mixture extracted from nacre of Haliotis laevigata. After incubation the mineral phase was dissolved and investigated for attached proteins. The results give a hint of one protein that seems to bind specifically to aragonite and not to calcite. The presented protocol seems to be suitable to detect mineral binding proteins quickly and therefore can point to proteins whose mineral binding capabilities should be investigated further.
Keywords: biomineralisation; biomineralising proteins; Haliotis; nacre; protein–mineral interaction